Penerapan Metode Bermain Kartu Kata untuk Meningkatkan Keterampilan Membaca Permulaan Siswa Kelas 1 SDN 1 Limboto - Irawati, Wa Ode; Masie, Sitti Rachmi (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
Abstract The study aims to improve the initial reading skills of SDN 1 Limboto 1st graders through the word card method. This study used the Classroom Action Research (CAR) method. The steps that will be performed in this PTK are in the form of a continuous loop. In this step, the researcher used the John Elliot model using two cycles. The research method is qualitative. The research project used consisted of 4 stages, namely: plan, implement, observe and reflect. This survey will be conducted in SD Negeri 1 Limboto, Kayubulan Village, Limboto District, Gorontalo District, Gorontalo Province. The subjects of this research were 1st year students, totaling 20 students. Data collection in this study includes observation techniques, interviews and documentation. Data analysis was performed in three steps: reduction, data description and conclusion. The results showed that the results of learning to read before action did not reach the goal of success. The percentage of obtaining the results of the initial reading before the action (pre-action) reached only 58.93%. After the action in cycle I, the results showed an increase with a percentage of 62.5%. In addition, cycle II showed a significant increase with a percentage of 78.57%. Therefore, the application of the word card game method can improve early reading skills in 1st grade SDN 1 Limboto. Keywords: card game, reading skills, 1st year students